2016
DOI: 10.7589/2015-04-084
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Galápagos Sea Lions (Zalophus wollebaeki) on San Cristóbal Island Rookeries Determined by Hematology, Biochemistry, Blood Gases, and Physical Examination

Abstract: The Galápagos sea lion, Zalophus wollebaeki, is an endemic and endangered species subject to population decline associated with environmental variability, such as El Niño events, constant feeding stress, and exposure to diseases through contact with introduced species. Reference blood parameter intervals have been published for some pinniped species, but baseline biochemical and blood gas values are lacking from Z. wollebaeki. We analyzed blood samples from 30 juvenile Galápagos sea lions (19 females, 11 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Other than the ocular trematodes, no sea lions evaluated had outward signs of disease except one that was comparatively thin. On bloodwork, values for the sea lions were like those previously established in Galapagos sea lions ( 16 ). Both PCV and point of care HCT were measured during this study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Other than the ocular trematodes, no sea lions evaluated had outward signs of disease except one that was comparatively thin. On bloodwork, values for the sea lions were like those previously established in Galapagos sea lions ( 16 ). Both PCV and point of care HCT were measured during this study.…”
Section: Discussionsupporting
confidence: 74%
“…Processing occurred on the same day as sampling. The blood samples were used for measuring various hematological parameters following the protocol used in this species by Páez-Rosas et al ( 16 ). Blood lactate was determined using a portable Lactate Plus TM analyzer (Nova Biomedical, Waltham, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These strategies include management to reduce the contact of humans and domestic dogs with sea lions, health studies in rookeries exposed and not exposed to human disturbances [52,53], the establishment of annual population monitoring in the entire archipelago, and the standardization of count methods. However, strategies for improving the quality of the marine and terrestrial habitats of sea lions have not been fully implemented.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…There are a few reports on marine mammals that indicate the differences in the hematological parameters between breeding and non-breeding seasons, or differences based on age [ 24 , 34 , 42 ]. We, therefore, compared the results of this study with information in the literature on the changes in the blood characteristics of California sea lions ( Zalophus californianus ) [ 3 , 4 ], Galapagos sea lions ( Zalophus wollebaeki ) [ 29 ], and Steller’s sea lions ( Eumetopias jubatus ) based on season or age [ 15 ]; however, these previous studies did not provide data that could refer to the results of this study. Gerlinsky et al (2018) reported that in Steller’s sea lions, erythrocytes tended to increase with growth, whereas leukocytes tended to decrease with growth and suggested that the changes in blood cell counts were related to the physiological state of the animals [ 15 ].…”
Section: Discussionmentioning
confidence: 99%